Digitizing Worship: Challenges of Religious Applications and Spiritual Decline in the Digital Era - Ruqayah, Farah; Setia, Paelani; Rosele, Muhammad Ikhlas (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2024)
This paper aims to analyze the impact of digitalization on the religious practices of Muslims through the use of religious applications, such as Muslim Pro, and to explore the challenges related to spiritual depth and community engagement. This research uses a qualitative method with data collection techniques through online observation of users' interactions with the application. The research findings show that while religious applications facilitate access to information and worship, there is a tendency for a decline in spiritual quality and community engagement, particularly in terms of social interaction and direct religious guidance. Over-reliance on these applications can reduce a deeper understanding of religion and weaken participation in collective religious activities. This research contributes by offering solutions that integrate technology with religious social interactions, involving collaboration between app developers, religious institutions, and communities to maintain a balance between digital convenience and spiritual needs.